Does the Satisfaction of ERP and Accounting Systems Users Differ? - Tuszkiewicz, Maciej Andrzej; Maruszewska, Ewa Wanda (Czy satysfakcja użytkowników systemów ERP i systemów księgowych się różni?, 2023)
This article aimed to check whether satisfaction, one of the measures of information systems’ effectiveness, varies among users of different Accounting Information Systems (AIS) types. The authors used End-User Computing Satisfaction (EUCS) questionnaire, and based on 248 responses found that ERP users scored higher satisfaction than accounting systems users only in the timeliness area. For both groups of respondents, ease of use had the lowest satisfaction scores. Based on the results, there were no significant differences in satisfaction between the ERP and accounting systems users. Additional differences between AIS users’ satisfaction scores were presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 4, s. 153-162
Keywords: Accounting Information Systems; AIS; accounting; user satisfaction; End-User Computing Satisfaction; EUCS; ERP; systemy informatyczne rachunkowości; rachunkowość; satysfakcja; kwestionariusz satysfakcji użytkowników końcowych